Emireriosis in young alpacas: Prevalence and risk factors - Rodríguez H., Antony (2012)
A total of 478 fecal samples taken from healthy alpaca crias aged 1-90 days at Centro de Investigación y Producción (CIP - La Raya), Universidad Nacional del Altiplano, Puno, were processed by the sedimentation and flotation technique in saturated sugar solution to detect oocysts and by the McMaster method to determine oocysts per gram (OPG) of fecal sample. Eimeria spp were present in 418 (87.5%) of the samples with a mean of 24,017 OPG (CI of 7,534 and range 50-1,202,400). The most frequent species were E. lamae (60.4%), E. macusaniensis (50.4%), E. alpacae (45.6%), E. punoensis (30%), and E. ivitaensis (6.24%). Parasite load increased with age, 50% of 24 samples at 1-30 days were positive with an average load of 17,216 OPG, at 31-45 days 93% of 82 (28,501 OPG), at 46-60 days 85% of 144 (34,731 OPG), at 61-75 days 94% of 183 (6,564 OPG) and at 76-90 days 80% of 45 with 17,376 OPG. E. lamae comprised 41% of all coccidian oocysts at 1-30 days and the highest rate of infection (66.7%) was reached at 46-60 days, whereas E. macusaniensis was present in only 4.2% of crias at 1-30 days, but peaked (65.6%) at 61-75 days. Double, triple, and quadruple infections were found in 28.2, 28.2, and 11.2% of positive samples respectively. The coexistence of E. lamae with E. alpacae and, E. lamae with E. macusaniensi infection were common in double infections, whereas E. lamae, E. alpacae and E. macusaniensis were mainly found in triple infections, and E. lamae, E. alpacae, E. punoensis and E. macusaniensis in quadruple infections. The multivariate logistic regression analysis showed that the age range of 1-30 days (OR=1.19, CI 95%: 0.08-0.48), 61-75 days (OR=2.49, CI 95%: 1.22-5.04) and separation of offsprings (OR=0.2, CI 95%: 0.08-0.48) were associated with Eimeria spp infection.